Sistem Informasi Pencatatan Pernikahan Menggunakan Sms Gateway - Fadila N Sagi; Mukhlisulfatih Latief; Rochmad Thohir Jassin (Diffusion: Journal of Systems and Information Technology, 2021)
FADILA N SAGI. Marriagge Registration Information System ( The Principal Suppervisor is Mukhlissulfatih Latief, S,Kom, MT., and the co-supervisior is Rachamad Thohir Jassin, S.Kom., Eng.)KUA (Kantor Urusan Agama or Office of Religios Affairs) of Ampana Tete Sub-district is a govemment institution serving to register mamage  process. Currently, the process is a paper- based work which tends to complicate officer in seeking certain data informing marriage schedule duc to the making requires the officer to look at the applicant's data one by one Consenquently, it may hamper a service quality to the community, in addition,  the complication applies to monthly and yearly reporting, which is a time- consuming process due to its making process involves a check data additionally, the mamage  data processing still operates Microsoft word and Microsoft Excel so that it leads to a frequent data duplication, data compt/lost, and also error committed by officer in registering the data. Another problem is that a penghulu ( Muslim Wendding offciant) often forgets abouts a must-do schedule. Objective of this research is to design a mamage registration information System at KUA of Ampana Tete Sub district. Data used in this research are descriptive data. Research finding is a mamage registration information system which facilitates and supports performace of KUA of Ampana Tete in processing and registering mamage data. Also, the community and penghulu  of KUA are earsier in accesing information about mamage data as well as mamage schedule due to the system functions SMS gateway technology.Keywoards :Mamage Registration Information System SMS gateway.